Isokinetic force of under-twenties soccer players: comparison of players in different field positions - Raphael Mendes Ritti Dias; Leandro Ricardo Altimari; Luiz Fernando Goulart (Universidade Federal de Santa Catarina, 2007)
During a soccer match, countless movements involving muscular force are performed. While some studies have analyzed the force exerted by soccer players, their results have been divergent, particularly when force has been analyzed with respect to fi eld positions. The objective of this study was to compare peak torque, total muscular work, maximum power and isokinetic fatigue index of the knee fl exor and extensor muscles of soccer players in a variety of fi eld positions. Seventy-eight under-twenty soccer players were classifi ed according to the position they play: goalkeepers (n=7), full backs (n=14), wingers (n=16), defensive midfi elders (n=11), center midfi elders (n=14) and forwards (n=16). The concentric isokinetic force of knee fl exor and extensor muscles was evaluated using an isokinetic dynamometer, Cybex® brand Norm™ 6000 model (CSMI, USA). Data was analyzed in terms of non-parametric statistics and results expressed in medians and semi-interquartile range. The Kruskal-Wallis test was applied and when results were signifi cant to p<0.05, the Mann-Whitney U test was used. Full backs' knee fl exor muscles exhibited lower peak torque, total muscular work and maximum power, when compared with the other positions, and defensive midfi elders' fl exor muscles had a greater fatigue index than the forwards'. Goalkeepers' knee extensor muscles exerted lower peak torque and had a higher fatigue index, when compared to results for the other positions. The results of this study indicate that there are differences in strength between players of different positions, especially full backs, defensive midfi elders and goalkeepers. This suggests that the soccer players' field positions have an infl uence on their levels of isokinetic force. RESUMO Durante uma partida de futebol são realizados inúmeros movimentos que envolvem a força muscular. Embora alguns estudos tenham analisado a força de jogadores de futebol, os resultados encontrados têm sido controversos, principalmente quando analisada a força em função da posição de jogo. O objetivo deste estudo foi comparar o pico de torque, trabalho muscular total, potência máxima e índice de fadiga isocinético dos músculos fl exores e extensores de joelho de jogadores de futebol que atuam em diferentes posições de jogo. Foram incluídos 78 atletas de futebol, pertencentes à categoria Sub-20, foram agrupados de acordo com a posição em campo de jogo: goleiros (n=7), zagueiros (n=14), laterais (n=16), volantes (n=11), meio campo (n=14) e atacantes (n=16). Foi realizada avaliação da força isocinética concêntrica dos músculos fl exores e extensores de joelho em dinamômetro isocinético da marca Cybex®, modelo Norm™ 6000 (CSMI, USA). A análise dos dados foi realizada por meio de estatística não-paramétrica sendo os valores expressos em mediana e semi-amplitude interquartílica. Foi empregado teste de Kruskal-Wallis e teste U de Mann-Whitney quando encontrados valores signifi cantes, com p<0,05. Nos músculos fl exores do joelho, observou-se menor pico de torque, trabalho muscular total e potência máxima nos zagueiros em comparação às outras posições e maior índice de fadiga dos laterais comparados aos atacantes. Nos músculos extensores de joelho, os goleiros apresentaram menor pico de torque e maior índice de fadiga comparado às demais posições. Os resultados do presente estudo indicaram diferenças na força entre as posições de jogo, especialmente nos zagueiros, laterais e goleiros. Essas informações sugerem que o posicionamento tático dos jogadores durante a partida, parece ter infl uência nos níveis de força isocinética em jogadores de futebol.